Adaptasi dan Stabilitas Hasil Galur-galur Aromatik Padi Sawah di Sumatera Utara - Akmal, Akmal; Gunarsih, Cucu; Samaullah, M. Yamin (Pusat Penelitian dan Pengembangan Tanaman Pangan, 2014)
This research was aimed to describe the yield stability and growth adaptation of elite lines of aromatic rice in rice production centers of North Sumatra. The experiments were conducted at 10 sites during dry season (DS) 2001 and DS 2002. Research materials consisted of 12 elite lines introduced from IRRI with IR64 as check variety. The treatments were arranged in a randomized block design (RBD) with three replications. Stability analysis was performed using methods of Eberhart and Russell, Finlay and Wilkinson, and Francis and Kanennberg. The results showed that the interaction of genotype x environment effect was very significant, indicating the presence of specific line adaptation on a particular environment. Genotypes which had the highest average yield were not always stable genotypes, as was shown by IR71137-49-1-2 which was more suitable to the sub-optimum environment. Lines IR71143-223-3-2-2-3, IR71146-97-1-2-1-3, IR65610-24-3-6-3-2-3, IR66696-49-1-2, IR71146-407-2-1-2-1, IR71146-122-1-1-2-1 were considered as stable genotypes according to the three analysis methods and each line showed high average yield. Those genotypes are suggested to be planted in the high productivity environments in order to obtain its optimum genetic expressivity on grain yield